Pan-European Study on the Prevalence of the Feline Leukaemia Virus Infection - Reported by the European Advisory Board on Cat Diseases (ABCD Europe) - Studer, Nadine; Lutz, Hans; Saegerman, Claude; Gönczi, Enikö; Meli, Marina L; Boo, Gianluca; Hartmann, Katrin; Hosie, Margaret J; Moestl, Karin; Tasker, Séverine; Belák, Sándor; Lloret, Albert; et al. (Viruses, 2019)
Feline leukaemia virus (FeLV) is a retrovirus associated with fatal disease in progressively infected cats. While testing/removal and vaccination led to a decreased prevalence of FeLV, recently, this decrease has reportedly stagnated in some countries. This study aimed to prospectively determine the prevalence of FeLV viraemia in cats taken to veterinary facilities in 32 European countries. FeLV viral RNA was semiquantitatively detected in saliva, using RT-qPCR as a measure of viraemia. Risk and protective factors were assessed using an online questionnaire to report geographic, demographic, husbandry, FeLV vaccination, and clinical data. The overall prevalence of FeLV viraemia in cats visiting a veterinary facility, of which 10.4% were shelter and rescue cats, was 2.3% (141/6005; 95% CI: 2.0%-2.8%) with the highest prevalences in Portugal, Hungary, and Italy/Malta (5.7%-8.8%). Using multivariate analysis, seven risk factors (Southern Europe, male intact, 1-6 years of age, indoor and outdoor or outdoor-only living, living in a group of ≥5 cats, illness), and three protective factors (Northern Europe, Western Europe, pedigree cats) were identified. Using classification and regression tree (CART) analysis, the origin of cats in Europe, pedigree, and access to outdoors were important predictors of FeLV status. FeLV-infected sick cats shed more viral RNA than FeLV-infected healthy cats, and they suffered more frequently from anaemia, anorexia, and gingivitis/stomatitis than uninfected sick cats. Most cats had never been FeLV-vaccinated; vaccination rates were indirectly associated with the gross domestic product (GDP) per capita. In conclusion, we identified countries where FeLV was undetectable, demonstrating that the infection can be eradicated and highlighting those regions where awareness and prevention should be increased.
Keywords: kočky; Protective Factors; Saliva; Cat Diseases; Risk Factors; sliny; prospektivní studie; Female; vaccination; Prevalence; Evropa; protective factors; Tumor Virus Infections; virus shedding; FeLV; Viremia; nemoci koček; infekce onkogenními viry; Leukemia Virus, Feline; retrovirové infekce; Prospective Studies; mužské pohlaví; Cats; RT-qPCR; Retroviridae Infections; zvířata; gross domestic product at purchasing power parity per capita; ženské pohlaví; prevalence; risk factors; Animals; Male; ochranné faktory; Europe; retrovirus; virus kočičí leukemie; veterinary sciences; viremie; rizikové faktory